Antigen-Specific Immunotherapy for Treatment of Autoimmune Liver Diseases - Richardson, Naomi; Ng, Sky T. H.; Wraith, David C. (Frontiers in Immunology, 2020)
The liver is a critical organ in controlling immune tolerance. In particular, it is now clear that targeting antigens for presentation by antigen presenting cells in the liver can induce immune tolerance to either autoantigens from the liver itself or tissues outside of the liver. Here we review immune mechanisms active within the liver that contribute both to the control of infectious diseases and tolerance to self-antigens. Despite its extraordinary capacity for tolerance induction, the liver remains a target organ for autoimmune diseases. In this review, we compare and contrast known autoimmune diseases of the liver. Currently patients tend to receive strong immunosuppressive treatments and in many cases, these treatments are associated with deleterious side effects. We propose that, in future, antigen-specific immunotherapies are adopted for treatment of liver autoimmune diseases in order to avoid such side effects. We describe various therapeutic approaches that either are in or close to the clinic, discuss their mechanism of action and assess their suitability for treatment of autoimmune liver diseases.